The Relationship Between Physical Activity And Hypertension Among The Elderly In The Muhammadiyah Regional Leadership (Pdm) Of Sleman - Ujang Candra Irawan; Indriani; Dika Rizki Imania (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Background: Hypertension, commonly referred to as high blood pressure, stands as a leading non-communicable disease responsible for a significant number of global fatalities and health issues. This condition constitutes a primary risk factor for various health complications, including heart disease, stroke, kidney disorders, and dementia. Hypertension frequently develops without noticeable symptoms, earning it the moniker "The Silent Killer." The prevalence of high blood pressure continues to increase, and low levels of physical activity are still a problem in Indonesia. Objective: The objective of this research was to examine the association between attributes such as age, gender, educational attainment, occupation, smoking habits, Body Mass Index (BMI), and physical activity concerning hypertension within the elderly population affiliated with the Muhammadiyah Regional Leadership (PDM) of Sleman. Method: The research utilized a descriptive methodology with a cross-sectional approach. Purposive sampling was employed to select a sample size of 120 elderly participants as respondents. Statistical analysis was conducted using the Chi-square Test. Results: The analysis findings indicate that most of the respondents display the following attributes: 45% are aged between 49 and 59 years, 87.5% are females, 45.8% have a secondary education, 45.8% are obese, 90% are non-smokers, 54.2% have a low level of physical activity, and 81.7% are diagnosed with stage 1 hypertension. There is a notable association between the level of physical activity and the prevalence of hypertension (p-value = 0.000). Conclusion: A connection exists between physical activity and hypertension among the elderly in the Muhammadiyah Regional Leadership (PDM) of Sleman.